Immersion and interaction during cycling in virtual reality: the influence on perceived effort and subjective experience - Colombo, Vera; Mondellini, Marta; Aliverti, Andrea; Sacco, Marco (Frontiers in Virtual Reality, 2025)
IntroductionVirtual Reality (VR) is a powerful tool for creating engaging and dynamic exercise environments that have the potential to change individuals' perception of effort during exercise. Despite its implications, especially in the rehabilitation field, a consensus on the factors related to VR that are most effective has not yet been reached in the literature.MethodsThe present study investigates how immersion and interaction influence perceived effort and subjective experience during exercise. Thirty-five young adults (age = 25.86 ± 4.96 y) participated in a single 40-min cycling session across four conditions: no VR, VR on a TV, VR with a headset, and VR with a headset plus an interactive task, all simulating a ride in a park.MethodsA comprehensive literature search was conducted across PubMed, Embase, Scopus, and the Cochrane Library, resulting in 46 eligible peer-reviewed studies published between 2014 and 2024. These studies included randomized controlled trials, quasi-experimental designs, and observational studies, with an average sample size of approximately 35 participants. The inclusion criteria focused on studies utilizing VR as a therapeutic modality for motor or executive function recovery in post-stroke populations.ResultsDespite a direct influence on the rate of perceived effort could not be observed, participants reported higher physical effort, represented by higher breathing rate, and higher attention, when immersion and interaction were combined. Despite slight side effects, people enjoyed and felt more present in most immersive VR conditions, making it their preferred way to exercise.DiscussionFuture works should continue in two directions: extending the protocol by including other target groups, e.g., patients, and exploring other VR features.